Management and outcomes of anastomotic leaks after oesophagectomy. Issue 8 (5th May 2016) - Dent, B; Griffin, S M; Jones, R; Wahed, S; Immanuel, A; Hayes, N
Abstract: Background: Leaks following oesophagectomy include true anastomotic leaks, leaks from the gastrotomy and gastric conduit necrosis. Historically, these complications were associated with high mortality rates. Recent improvements in outcome have been attributed to the wider use of oesophageal stents in patient management. This study examined outcomes of patients who developed a leak in a single high-volume institution that did not use stenting as a primary treatment modality. Methods: All patients undergoing an oesophagectomy between January 2009 and December 2013 were included. Patients were identified from a prospectively maintained database. Results: A total of 390 oesophagectomies were performed (median age 65 (range 32–81) years). In 96·7 per cent of patients this was a two-stage subtotal oesophagectomy. Overall in-hospital and 90-day mortality rates were both 2·1 per cent (8 patients). Some 31 patients (7·9 per cent) developed a leak (median age 64·5 (range 52–80) years), of whom 27 (87 per cent) were initially managed without surgery, whereas four (13 per cent) required immediate thoracotomy. The median length of stay for patients with a leak was 41·5 (range 15–159) days; none of these patients died. Conclusion: Leaks can be managed with excellent outcomes without using oesophageal stents. The results do not support the widespread adoption of endoscopic stenting. Abstract : No need for stenting